Influence of methoxylation on the anti-diabetic activity of ρ-hydroxybenzaldehyde in type 2 diabetic rat model - Ahmed Olatunde; Aminu Mohammed; Mohammed Auwal Ibrahim; Mohammed Nasir Shuaibu (Elsevier, 2021)
The present study was designed to investigate the role of methoxylation on the anti-diabetic potential of ρ-hydroxybenzaldehyde (ρ-BN) and its derivatives vanillin (VN) and syringaldehyde (SN) in type 2 diabetes (T2D). Fructose-fed streptozotocin-induced T2D rat model was used and orally treated with 50 and 100 mg/kg body weight of ρ-BN, VN and SN for 28 days. From the results, the diabetic control (DBC) group showed significant (p < 0.05) elevation in insulin resistance, blood glucose, fructosamine, glycogen phosphorylase (GP) activity, lipid profiles, and a significant (p < 0.05) decrease in β-cell functions, insulin, liver glycogen contents, and glycogen synthase (GS) activity. The insulin receptor substrate-1 (IRS-1) and glucose transporter-4 (GLUT-4) mRNA expression in the hepatocyte and skeletal muscle were decreased in DBC group compared to the normal control (NC) group. Oral treatment of the compounds improved the above diabetes-induced alterations to near normal and were comparable to the metformin treated group. Variation in methoxylation of ρ-BN, VN, and SN displayed an inconsistent pattern on the measured indices of diabetes (insulin resistance, β-cell functions, blood glucose, insulin, fructosamine, GS, GP, lipid profiles, IRS-1 and GLUT-4). However, in the case of oral glucose tolerance ability, serum insulin and fructosamine levels, liver glycogen contents and cardiovascular risk indices, the methoxylation mediated positive effects. The phenolic aldehydes (ρ-BN, VN, and SN) possessed anti-T2D activity while methoxylation partly influenced the anti-diabetic effects of the phenolic aldehyde skeleton.